Odor-evoked inhibition of olfactory sensory neurons drives olfactory perception in Drosophila. Issue 1 (December 2017) - Cao, Li-Hui; Yang, Dong; Wu, Wei; Zeng, Xiankun; Jing, Bi-Yang; Li, Meng-Tong; Qin, Shanshan; Tang, Chao; Tu, Yuhai; Luo, Dong-Gen
Abstract Inhibitory response occurs throughout the nervous system, including the peripheral olfactory system. While odor-evoked excitation in peripheral olfactory cells is known to encode odor information, the molecular mechanism and functional roles of odor-evoked inhibition remain largely unknown. Here, we examinedDrosophila olfactory sensory neurons and found that inhibitory odors triggered outward receptor currents by reducing the constitutive activities of odorant receptors, inhibiting the basal spike firing in olfactory sensory neurons. Remarkably, this odor-evoked inhibition of olfactory sensory neurons elicited by itself a full range of olfactory behaviors from attraction to avoidance, as did odor-evoked olfactory sensory neuron excitation. These results indicated that peripheral inhibition is comparable to excitation in encoding sensory signals rather than merely regulating excitation. Furthermore, we demonstrated that a bidirectional code with both odor-evoked inhibition and excitation in single olfactory sensory neurons increases the odor-coding capacity, providing a means of efficient sensory encoding. It is well established that odor-evoked excitation in olfactory sensory neurons (OSNs) encodes odor information. Here the authors report that odor-evoked inhibition in OSNs of Drosophila also encodes odor identity, and can in itself drive both attraction and avoidance behaviors.